Analysis Of Customer's Interest In Selecting Paid Products In PT. Hasanuddin Gowa Branch Syriah Pegadaian - Nasrullah Nasrullah; Firna Figriyanti (Jurnal Ar-Ribh, 2022)
This study uses a qualitative research method, which aims to find out how customers are interested in choosing a pawn product that has been provided by the pawnshop. This research was carried out at PT. Pegadaian Syariah Hasanuddin Gowa Branch which took place from March 21, 2022. Data collection techniques in this study used library research and field research such as observations and interviews. Pegadaian is a guarantee institution that is very well known in people's lives in an effort to obtain funds to facilitate various transaction needs. The presence of sharia pawnshops as a formal financial institution in the form of a unit of pawnshops in Indonesia, which is tasked with distributing financing in the form of providing loan money to people in need based on sharia pawn law is something that needs to get a positive response.